(3GdEbJUGO GdLRFjs - (3eMeO UahJ(B, (3bGHds ([(3O(B.(3e(B]:s [(3f(B.(3f(B],s, 2008)
(3jVe eGgjI GdEbJUGO, GdfXGe GdEbJUGOj, GdSdY hGdNOeGJ, GdeTcdI GdEbJUGOjI, eMOOGJ GdWdH heQhfI GdWdH, eMOOGJ GdYQV, eQhfI GdYQV, cjajI JMOjO SYQ GdJhGRf , Sdhc GdeSJgdc, OGdI GdEfJGL, OGdI GdJcGdja , JhGRf GdefJL aj Shb GdefGaSI GdcGedI, JhGRf GdefJL aj Shb GdEMJcGQ, GdefGaSI GdEMJcGQjI, GMJcGQ GdbdI, GdJhRjYs
Keywords: (3GdCSYGQs; (3GdEbJUGOs; (3GdEbJUGO GdLRFjs; (3GdefGaSIs